Correlation between the event of the COVID-19 pandemic and symptoms of anxiety, depression and temporomandibular disorder in university students: cross-sectional study - Soares, Lélio Fernando Ferreira [UNESP]; Castro, Jordanna Victtória; Andrade, Loren Dos Santos [UNESP]; Ramos, Marcela De Come [UNESP]; Almeida, Daniel Augusto De Faria; Haddad, Marcela Filié (Sociedade Brasileira para o Estudo da Dor, 2023)
78.2% of participants with symptoms of anxiety and 54.5% of participants with symptoms of depression reported a high level of parafunction, while 71.5% of participants who reported painful TMD symptoms had symptoms of anxiety and 52% of depression.The presence of anxiety symptoms was more prevalent than depression among participants with painful symptoms associated with TMD.This study has provided insights into the impact of the COVID-19 pandemic on painful TMD symptoms in university students and the influence of psychological factors such as anxiety and depression.The results observed in this study indicate consequences that may perpetuate after the COVID-19 pandemic period and instigate further studies.
Keywords: Anxiety; COVID-19; Depression; Temporomandibular joint dysfunction syndrome